Dietary Assessment with a Wearable Camera among Children: Feasibility and Intercoder Reliability - Beltran, Alicia; Dadabhoy, Hafza; Ryan, Courtney; Dholakia, Ruchita; Jia, Wenyan; Baranowski, Janice; Sun, Mingui; Baranowski, Tom (Journal of the Academy of Nutrition and Dietetics, 2018)
The eButton, a multisensor device worn on the chest, uses a camera to passively capture images of everything in front of the child throughout the day. These images can be analyzed to provide a passive method of dietary intake assessment. This study assessed the eButton’s feasibility and intercoder reliability for dietary intake assessment. Children were recruited in the summer and fall of 2015, in Houston, TX, to wear the eButton to take 2 full days of dietary images, and the child–parent dyad participated in a following-day interview to verify what dietitians recorded from the images. Thirty 9- to 13-year-old children participated during days convenient to them. Two dietitians independently manually reviewed the images to identify eating events, foods in those events, and portion sizes. Descriptive statistics of agreements and disagreements were calculated between dietitians and with children; t tests and Bland-Altman plots of differences in total kilocalories were calculated between dietitians and between initial dietitian estimates and those finalized after the verification interviews. The dietitians agreed on the identity of 60.5% of the 1,026 foods but disagreed on 28.6% of the foods and on the names for 10.8% of the foods. After the verification interviews, the dietitians agreed with the child–parent dyads on the identity of 77.0% of the 921 foods; the child–parent dyad identified 12.4% of the day’s foods when images were not available or not clear; the child–parent dyad clarified that 5.4% of the foods identified were not consumed by the child; and the child–parent dyad clarified the identity of 5.2% of the foods. A software-based approach (three-dimensional wire mesh) could be used to estimate portion size on 24% of the foods, and professional judgment was required for 67.8%. Mean caloric intakes per day were not statistically significantly different between dietitians but were different between dietitians and child–parent dyads in total and on day 2. An early test of intercoder reliability of an all-day image method of dietary intake assessment obtained intercoder agreement between the two dietitians processing these images of intraclass correlation coefficient=0.67. A following-day verification interview with the child and parent was necessary to ensure completeness of estimates. Several feasibility problems occurred, which may be remedied with additional participant and dietitian training and further technological development.